Analysis of Health Care Personnel's Attitudes Toward Complementary and Alternative Medicine and Life Satisfaction due to COVID-19 Pandemic - Teke, Neslihan; Ozer, Zulfunaz; Bahcecioglu Turan, Gulcan (Lippincott Williams & Wilkins, 2021)
This study was conducted to analyze health care personnel's attitudes toward traditional and complementary medicine (TCM) and life satisfaction due to coronavirus disease-2019 (COVID-19) pandemic. This cross-sectional descriptive study was conducted between April 2 and 9, 2020. The Questionnaire form was sent to health care personnel online. A total of 560 individuals who answered the questionnaires were included in the study. The data were collected by using the Personal Information Form, Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ), and Life Satisfaction Scale (LSS). Average age of the participants was 30.88 +/- 7.68 years, 82.5% were male, and 65.5% were working as nurses. It was found that 45.5% of the participants used TCM methods for COVID-19 during the last month; 48.7% of the health care personnel stated that they used TCM methods to strengthen their immune system. The HCAMQ total average score was 27.96 +/- 5.49; the holistic health subdimension total average score was 9.59 +/- 3.04; the complementary and alternative medicine subdimension total average score was 18.37 +/- 3.58; and the LSS total average score was 20.78 +/- 6.32. A positive weak statistically significant association was found between the HCAMQ and complementary and alternative medicine subdimension and the LSS (P < .05). Participants had moderately positive attitudes toward TCM and life satisfaction. As the participants' positive attitudes toward TCM increased, their life satisfaction was also found to increase.
Keywords: COVID-19; health care personnel; life satisfaction; traditional and complementary medicine